AMC-Loaded Low-Profile Broadband Printed 2×2 Array With Gain and Isolation Enhancement Using Equivalent Circuit Model for Wireless Systems - Hossein Malekpoor (IEEE Access, 2023)
A $2× 2$ array of printed antenna loaded by planar Giuseppe Peano artificial magnetic conductor (AMC) is presented for vehicular wireless systems. The four-element of the proposed array by utilizing diverse polarized directions of the printed dipoles with a $5× 5$ AMC reflector achieves a wideband antenna with enhanced properties. It shows the measured S-parameters of the wide bandwidths from 3.30 to 6.02 GHz with increased stable gains and efficiencies (more than 90%) for all elements. Moreover, the appropriate isolation of greater than 30 dB between the elements is achieved. The proposed design of the printed dipoles includes T-shaped microstrip dipoles and a feedline system as a T-shape to broaden the bandwidth in 4.7-6.02 GHz ( $\text{S}_{11}\le $ -10 dB). By utilizing the $3× 3$ Giuseppe Peano AMC reflector into the one element of the printed dipole, enhanced radiation efficiency and −10 dB measured bandwidth from 3.26 to 6.02 GHz (60%) is achieved for vehicular wireless systems. The proposed design with AMC with respect to the antenna without AMC indicates a reduced size of 70%, increased gain up to 8.4 dBi, and uni-directional radiation patterns. The new AMC unit cell is configured by the Giuseppe Peano design to resonate at 5.36 GHz in 4.27-6.34 GHz (39%). Finally, the suggested equivalent transmission line model of the $2× 2$ array with AMC surface is introduced with a suitable agreement between the results of reflection coefficients.